Study of metopic suture in south Indian skulls - Basha, Moula P. Akbar; Sugavasi, Raju (International Journal of Research in Medical Sciences, 2017)
Background: The cranial sutures and their development is the most interesting in the field of cranial growing and shaping. Metopism is partially or totally persisting suture extending from the nasion to the anterior angle of the bregma of frontal bone. Methods: Total 100 human adult dry skulls were collected from south India for present study to find out the incidence of metopic suture. Results: Out of 100 skulls, found one complete and one incomplete metopic suture. Conclusions: Present study may be useful for diagnostic and surgical intervention, particularly during frontal craniotomy.